2021
DOI: 10.1111/vop.12933
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of tear film breakup time measurements in normal dogs using three different methods of fluorescein solution administration

Abstract: Objective To evaluate whether the method of fluorescein administration affects the results of tear film breakup time (TFBUT) measurement in normal dogs. Animals studied Thirty‐seven client and hospital staff owned dogs over 1 year of age with no known comorbidities or administration of systemic or topical ophthalmic medications. Procedures A prospective randomized three‐way crossover study was conducted. All dogs received an abbreviated ophthalmic examination to rule out ocular surface disease. Using a 30‐min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…In the current study, the authors used diluted fluorescein sodium. A recently published study reported no difference in mean TBUT between different methods of fluorescein sodium application 12 . By reviewing the literature, mean TBUT values for normal dogs have also been reported to be 5.9–8.6 s, 13 which was similar to the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the authors used diluted fluorescein sodium. A recently published study reported no difference in mean TBUT between different methods of fluorescein sodium application 12 . By reviewing the literature, mean TBUT values for normal dogs have also been reported to be 5.9–8.6 s, 13 which was similar to the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…This study was conducted on 19 different dog breeds including Pomeranian (7), English Cocker Spaniel (7), Shih Tzu (24), Yorkshire Terrier (1), West Highland White Terrier (12), Maltese (1), Japanese Spitz (3), English Bulldog (2), Dachshund (1), Miniature Poodle (1), Chihuahua (3), Pekingese (9), Chow chow (1), Japanese Akita (1), Pug (3), King Charles Cavalier Spaniel (1), Golden Retriever (3), French Bulldog (1), and German Shepherd (1).…”
Section: Demographic Datamentioning
confidence: 99%
“…Although the quantity of tear secretion is adequate in Shih Tzu dogs, the quality of tear film appears to be compromised in this breed. Tear film breakup time, a subjective measurement of tear quality, was much lower in the present study of Shih Tzu dogs (mean 5.3 s) compared with normative data from previous studies (mean ranges from 16.0 to 21.5 s) 43–45 . This important finding could be explained by three main factors: breed‐related conformation, low conjunctival goblet cell density (reduced pre‐ocular mucins) 16 and meibomian gland dysfunction (altered tear film lipids) 12,46 .…”
Section: Discussioncontrasting
confidence: 65%
“…Tear film breakup time, a subjective measurement of tear quality, was much lower in the present study of Shih Tzu dogs (mean 5.3 s) compared with normative data from previous studies (mean ranges from 16.0 to 21.5 s). [43][44][45] This important finding could be explained by three main factors: breed-related conformation, low conjunctival goblet cell density (reduced pre-ocular mucins) 16 and meibomian gland dysfunction (altered tear film lipids). 12,46 First, several anatomical features of Shih Tzu eyes (e.g., exophthalmos, macropalpebral fissure, and lagophthalmos) promote tear film evaporation owing to excessive exposure of the ocular surface.…”
Section: F I G U R E 3 Meanmentioning
confidence: 99%
“…In humans, it is generally recommended to apply a minimal amount of fluorescein to improve test reliability 80 . In dogs, however, TFBUT values were relatively similar whether one or two drops of fluorescein were applied to the ocular surface, 81 a species difference that is likely due to larger tear volume in dogs compared to humans 82 …”
Section: Measurement Of Tear Qualitymentioning
confidence: 99%